Evaluasi Mutu dan Kemurnian Madu Tawon yang Beredar di Kota Semarang - Ch Retnaningsih; Vera Handayani; Lucia Sri Lestari (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
Honey is a thick liquid that are collected, moded and condensed by honey bees from the nectar source. Along with its fame, honey that are distributed now a days appear in different kind of quality and variety. The aim of the study was to determine the quality of commercial honeys distributed in Semarang and compared with fresh honey. Samples of honey covered 6 brands of commercial honey and 3 brands of honey of